2000
DOI: 10.1002/1096-8628(20000612)96:3<360::aid-ajmg24>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

5-HT2a receptor polymorphism gene in bipolar disorder and harm avoidance personality trait

Abstract: The purpose [corrected] of this study was to investigate the relationship between bipolar disorder and the harm avoidance personality trait (HA), and the genetic contribution of the polymorphic DNA variation T102C in exon 1 of 5-HTR2a (chromosome 13q14-21) in bipolar disorder and HA personality trait. Forty bipolar patients and 89 normal subjects completed the TPQ questionnaire and were genotyped for 5-HT2a. Bipolar patients scored higher than normal subjects on the HA dimension. However, no contribution of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 23 publications
3
30
0
1
Order By: Relevance
“…On the other hand, Sato et al (2001) demonstrated that the TCI has a high internal consistency and a factor structure that is robust against mild to moderate states of depression (as it is in this study). Although we studied mostly symptomatic BD patients, our results replicated most of the previous findings of temperament and character traits in euthymic BD subjects (Young et al, 1995;Osher et al, 1996;Osher et al, 1999;Blairy et al, 2000;Engstrom et al, 2004a;Evans et al, 2005). Therefore, although mood state effects are possible, it is unlikely that they explain our findings of personality differences between BD patients and healthy individuals.…”
Section: Personality Differences In Bipolar Disorder With Comorbid Alsupporting
confidence: 89%
See 2 more Smart Citations
“…On the other hand, Sato et al (2001) demonstrated that the TCI has a high internal consistency and a factor structure that is robust against mild to moderate states of depression (as it is in this study). Although we studied mostly symptomatic BD patients, our results replicated most of the previous findings of temperament and character traits in euthymic BD subjects (Young et al, 1995;Osher et al, 1996;Osher et al, 1999;Blairy et al, 2000;Engstrom et al, 2004a;Evans et al, 2005). Therefore, although mood state effects are possible, it is unlikely that they explain our findings of personality differences between BD patients and healthy individuals.…”
Section: Personality Differences In Bipolar Disorder With Comorbid Alsupporting
confidence: 89%
“…While higher harm avoidance has been consistently linked to mood disorders in general (Cloninger et al, 1994;Brown et al, 1992;Joffe et al, 1993;Hirano et al, 2002), and with bipolar disorder in particular (Blairy et al, 2000;Osher et al, 1996;Osher et al, 1999;Engstrom et al, 2004a;Evans et al, 2005), higher novelty seeking in bipolar patients compared to both unipolar patients and healthy individuals has been reported by one study (Young et al, 1995). In the same study, bipolar patients presented higher novelty seeking than unipolar patients, and both groups had higher harm avoidance than the healthy control group, indicating that the combination of higher novelty seeking and harm avoidance might be a characteristic of bipolarity.…”
Section: Personality Differences Between Bipolar Patients and Healthymentioning
confidence: 99%
See 1 more Smart Citation
“…This was between avoidance traits and the 5HTT LPR polymorphism (P ¼ 0.038). A crude estimate of the effect size of 26 Control participants not scored for personality Benjamin et al 34 Data reported elsewhere Benjamin et al 43 Subscale data reported only Blairy et al 45 Too few papers reporting data on this gene to analyse Comings et al 36 Data reported elsewhere Comings et al 19 Subscale data reported only Comings et al 47 Too few papers reporting data on this gene to analyse Damberg et al 48 Subscale data reported only Deary et al 27 Extreme scores design Duaux et al 32 Data not released Ekelund et al 28 Extreme scores design Gustavsson et al 57 Subscale data reported only Jang et al 40 Data reported elsewhere Jonsson et al 63 Subscale data reported only Jonsson et al 62 Subscale data reported only Jonsson et al 61 Subscale data reported only Jonsson et al 29 Subscale data reported only Jorm et al 65 Too few papers reporting data on this gene to analyse Lerman et al 31 Data not released Manuck et al 73 Too few papers reporting data on this gene to analyse Manuck et al 72 Too few papers reporting data on this gene to analyse Mel et al 35 Data reported elsewhere Melke et al 74 Subscale data reported only Nielsen et al 77 Subscale data reported only Persson et al 30 Subscale data reported only Persson et al 81 Too few papers reporting data on this gene to analyse Ricketts et al 83 Data reported elsewhere Sher et al 38 Data reported elsewhere Sirota et al 37 Data reported elsewhere Strobel et al 24 Data reported elsewhere Tsai et al 89 Too few papers reporting data on this gene to analyse Vandenbergh et al 90 Extreme scores design the 5HTT LPR polymorphism on avoidance traits suggested that the genotypic effect accounted for less than 10% of the phenotypic variance, but this figure should ...…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Studies employing the Temperament and Character Inventory (TCI) or the Tridimensional Personality Questionnaire (TPQ) reported that patients with BD showed higher scores on Harm avoidance than did controls. 6,[8][9][10][11][12][13][14] Regrettably, none of these studies presented separate data on BD I and BD II patients; rather, subjects included mixed BDI and BD II patients or only those with BD I. As BD II differs from BD I in genetic, [15][16][17] biological, 18 neuropsychological, 19 and clinical [20][21][22] aspects, the personality traits of individuals with BD II and BD I should be assessed separately.…”
Section: Introductionmentioning
confidence: 85%